Perlindungan Hukum Terhadap Konsumen Pengguna Jasa Angkutan Udara - Y. D.W. Susi Irianti; Sella Petrix Pelupessy (BULLET : Jurnal Multidisiplin Ilmu, 2025)
The research, entitled "Legal Protection for Consumers Using Air Transportation Services," was conducted with the aim of identifying and clearly understanding the types of violations committed by air transportation service providers and seeking a formulation of legal protection that is perceived as fair for consumers using air transportation services from a business law perspective. This research is empirical juridical because it does not view consumer protection law and air transportation law as normative regulations or legal principles in conducting business activities. Rather, it views them as social institutions, examining how these two legal instruments, along with other complementary legal instruments, operate within society. The results revealed that the types of violations committed by air transportation service providers include the provision of false information by ticket sales staff with the aim of deceiving prospective passengers (consumers) into purchasing significantly more expensive executive class tickets; irrational price changes at specific times (sometimes within less than 24 hours); and the placement of standard clauses in airline tickets, which are the air transportation documents, which in practice significantly burden consumers using air transportation services. Therefore, it is necessary to create a consumer protection system that contains elements of open access and information as well as guarantees of legal certainty regarding consumer disputes, either through the Consumer Dispute Resolution Agency or through the District Court in the jurisdiction where the consumer is domiciled.